Mare, fiume, ruscello Acqua e musica nella cultura romantica - Stöckle, Susanne Magdalena (Biblioteca di Studi di Filologia Moderna, 2018)
Mare, fiume, ruscello. Acqua e musica nella cultura romantica (Sea, river, stream. Water and music in romantic culture) re-reads German literature between the 18th and 19th centuries, focusing on the figure of water, following the theoretical-methodological lines traced by Gaston Bachelard in his studies on material imagination, especially in his 1942 work L'eau et les rêves. The work investigates the elective affinities between liquid substance, poetic word and music in the romantic period. The rereading highlights the large number of "liquid-aquatic" metaphors in Franz Schubert's lieder works, with particular attention to the cycles Die Schöne Müllerin (1823) and Winterreise (1828). The study is conducted in an interdisciplinary perspective that extends, between literary and musical analysis, to the reading and listening of the Lieder.